2021
DOI: 10.3390/jcm10153333
|View full text |Cite
|
Sign up to set email alerts
|

Calculated Plasma Volume Status Is Associated with Adverse Outcomes in Patients Undergoing Transcatheter Aortic Valve Implantation

Abstract: Background: Calculated plasma volume status (PVS) reflects volume overload based on the deviation of the estimated plasma volume (ePV) from the ideal plasma volume (iPV). Calculated PVS is associated with prognosis in the context of heart failure. This single-center study investigated the prognostic impact of PVS in patients undergoing transcatheter aortic valve implantation (TAVI). Methods: A total of 859 TAVI patients had been prospectively enrolled in an observational study and were included in the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Notably, the same cut-off was the basis for a study in 600 TAVI patients, where patients with an ePVS past this cut-off also demonstrated significantly worse postinterventional outcomes (46). Slightly lower ePVS cut-offs in the same range were proposed by Martens et al and Seoudy et al (23,33). In the study conducted by Martens et al on a large cohort of heart failure patients the measured plasma volume and calculated ePVS were found to be comparable (23).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Notably, the same cut-off was the basis for a study in 600 TAVI patients, where patients with an ePVS past this cut-off also demonstrated significantly worse postinterventional outcomes (46). Slightly lower ePVS cut-offs in the same range were proposed by Martens et al and Seoudy et al (23,33). In the study conducted by Martens et al on a large cohort of heart failure patients the measured plasma volume and calculated ePVS were found to be comparable (23).…”
Section: Discussionmentioning
confidence: 85%
“…In their mixed cohort of patients with HFpEF, heart failure with a mid-range (HFmEF) and reduced ejection fraction (HFrEF), a −6.5 cut-off was identified as the optimal cut-off in terms of heart failure related hospitalization and allcause mortality (23). Seoudy et al identified an ePVS cut-off of −5.4 as a significant predictor of these outcomes in a TAVI cohort at 1 year after the intervention (33). Interestingly, Schaefer et al identified a higher ePVS cut-off of 3.1 when analyzing the correlation of the calculated plasma volume status with shortand long-term outcomes in patients undergoing mitral valve surgery (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, plasma volume status (PVS), which is calculated from non-invasive biomarkers of hematocrit and body weight, has been shown to be moderately correlated with gold-standard measurements using radioisotope assays (16). Previous studies have revealed that PVS was associated with clinical outcomes of heart failure (17), transcatheter aortic valve implantation (18), and cardiovascular diseases (19). However, few research studies have investigated the association between PVS and the risk of poor outcomes in AIS patients treated with EVT.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue of the Journal of Clinical Medicine (JCM) entitled “Transcatheter Structural Heart Disease Interventions: Clinical Update” offers eight original articles and four review articles. Ten articles focus on the transcatheter aortic valve approach, discussing all the relevant issues related to this technique, such as balloon aortic valvoplasty [ 15 ]; TAVI indications and patient selection [ 16 ]; pre-procedural planning [ 17 ]; access routes (open or percutaneous vascular access) [ 18 ]; potential access-related complications [ 19 ]; TAVI outcomes compared with surgery [ 20 ]; challenges of surgery after TAVI failure [ 21 ]; post-TAVI prognostic factors [ 22 ]; potential benefits of cerebral embolic protection devices [ 23 ]; and the BASILICA technique to prevent coronary obstruction [ 24 ]. Three additional articles discuss the state of the art in transcatheter mitral valve replacement images [ 25 ]; atrial functional tricuspid regurgitation [ 26 ]; and the use of different diagnostic catheters for transradial coronary angiography [ 27 ].…”
mentioning
confidence: 99%